Corona characteristics of conductor with TiO2 hydrophilic film subjected to DC high voltage. Issue 16 (18th December 2018) - Bian, Xingming; Lin, Yaoyu; Pi, Xinan; Lu, Tiebing; Xu, Feifei; Li, Haibing; Ma, Yanxiang
Abstract : Water drops on the surface of conductors influence the ambient electric fields and decrease corona inception voltage. A conductor coated with TiO2 film was developed to prevent effects of droplets. The corona inception voltage of conductors in different conditions was measured. The experiments were designed to study effects of three factors including UV‐light, the position of water drops, and mass fraction of TiO2 on corona discharge. The influences on the three factors to the corona inception discharge were summarised. Different processes of corona occurred when a water drop on upper or lower surface of the conductor. The contact angle is smaller when the conductor is coated with the paint containing TiO2 because TiO2 is hydrophilic under UV‐light. UV‐light can improve TiO2 's hydrophilia. The ingredients of the paint are insulated. These ingredients prevent the adsorption of space charge and enlarge ionisation layers, thus the corona discharge will be restrained. With the increase of TiO2 's mass fraction under the UV‐light, the impact of water drops to discharge is further inhibited and the corona inception discharge voltage is increased.